Implementation Of Green Human Resource Management As The Key To UMKM Actors' Compliance With Government Green Political Regulations - Sri Kumala Dewi; Waldi Putra; Yuni Candra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the implementation of Green Human Resource Management (GHRM) in Micro, Small, and Medium Enterprises (MSMEs) and evaluate its effectiveness in driving compliance with the government's Green Politics regulations. The research method employed is descriptive qualitative with a document study approach, utilizing content analysis on environmental regulations, industry reports, and relevant secondary literature. The results indicate that the adoption level of GHRM in MSMEs remains at a simple functional adaptation stage through digital efficiency (paperless billing), energy conservation, and the use of eco-friendly packaging, all driven by the interpersonal directing function of business owners. This internal practice proves to be a crucial instrument in meeting local regulations, such as single-use plastic bans, while simultaneously mitigating legal risks. The novelty of this study lies in its shift of analytical focus; while previous research predominantly focused on complex GHRM systems in large corporations with established structures, this study demonstrates that simplifying cost-efficient GHRM practices in the informal sector can serve as a strategic bridge for external regulatory compliance. The implication of this study demands government intervention in knowledge management through free green training and economic incentives, rather than merely enforcing punitive sanctions, to foster a compliant and sustainable MSME ecosystem.